Asymmetric Information and Differentiated Durable Goods Monopoly: Intra-Period Versus Intertemporal Price Discrimination - Didier Laussel; Ngo Van Long; Joana Resende (Center for Economic Studies and ifo Institute (CESifo), 2021)
A durable good monopolist faces a continuum of heterogeneous customers who make purchase decisions by comparing present and expected price-quality offers. The monopolist designs a sequence of price-quality menus to segment the market. We consider the Markov Perfect Equilibrium (MPE) of a game where the monopolist is unable to commit to future price-quality menus. We obtain the novel results that (a) under certain conditions, the monopolist covers the whole market in the first period (even when a static Mussa-Rosen monopolist would not cover the whole market), because this is a strategic means to convince customers that lower prices would not be offered in future periods, and that (b) this can happen only under the stage-wise Stackelberg leadership assumption (whereby consumers base their expectations on the value of the state variable at the end of the period). Conditions under which MPE necessarily involve sequentially trading are also derived.
Keywords: C73; D42; L12; 330; product quality; durable good monopoly; second-degree price discrimination; Coase conjecture